Advancing antibody-drug conjugates in gynecological malignancies: myth or reality? - Marta Nerone; Maria Del Grande; Cristiana Sessa; Ilaria Colombo (Exploration of Targeted Anti-tumor Therapy, 2022)
Antibody-drug conjugates (ADCs) represent a new class of therapeutic agents designed to target specific antigens on tumor cells, combining the specificity of monoclonal antibodies to the cytotoxicity of classic chemotherapy agents. These drugs have been extensively studied both in solid and hematologic malignancies, leading to substantial improvement in the therapeutic landscape for several tumors. Despite no ADC have been yet approved for the treatment of gynecological malignancies, some agents have shown promising results and might have the potential to become part of the standard of care. Among them, mirvetuximab soravtansine has shown activity in platinum-resistant ovarian cancer with high folate-α receptor expression, as a single agent and in combination. Tisotumab vedotin is active in patients with pre-treated cervical cancer, and further investigation is ongoing. The purpose of this review is to summarize the structural and functional characteristics of ADCs and analyze the most recent and promising data regarding the clinical development of ADCs in gynecological malignancies. The available data on the efficacy of the more studied ADCs in ovarian, endometrial, and cervical cancers will be discussed along with toxicities of special interest, the mechanisms of resistance, and future possible drugs combination.